1994
DOI: 10.1103/physrevd.50.6730
|View full text |Cite
|
Sign up to set email alerts
|

Property of recombination in polarized hadronic targets

Abstract: The triple gluon-ladder vertex is shown to project the outgoing gluon in either polarization state with equal probability up to the leading double-ln(x)ln(Q2) approximation. This implies that the Q2 evolution of AG(x, Q2) is free from recombination effects to this level of approximation.PACS number(s): 13.60. Hb, 12.38.Cy, 13.88.+e

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Unfortunately more recently we showed [6] that the magnetic field decayed fast enough not to be able to seed galactic dynamos. Earlier, Barrow and Tsagas [7] showed that in open Friedmann universes, magnetic fields decay slower, therefore this mechanism is able to help obtaining cosmic magn etic fields strong enough to seed the galactic dynamo beyond inflation [8]. Even earlier, Turner and Widrow [1] proposed a Lagrangean in pseudo-Riemannian spacetime to generate primordial magnetic fields which could obtain extremely weak seed fields of the order of 10 −65 G through the presence of a tiny photon mass, which clearly are extremely weak to seed galactic dynamos.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately more recently we showed [6] that the magnetic field decayed fast enough not to be able to seed galactic dynamos. Earlier, Barrow and Tsagas [7] showed that in open Friedmann universes, magnetic fields decay slower, therefore this mechanism is able to help obtaining cosmic magn etic fields strong enough to seed the galactic dynamo beyond inflation [8]. Even earlier, Turner and Widrow [1] proposed a Lagrangean in pseudo-Riemannian spacetime to generate primordial magnetic fields which could obtain extremely weak seed fields of the order of 10 −65 G through the presence of a tiny photon mass, which clearly are extremely weak to seed galactic dynamos.…”
Section: Introductionmentioning
confidence: 99%